Ethos, speech, media. Semiotics of ethos - Soulez, Guillaume (Universidad de Chile. Instituto de la Comunicación e Imagen, 2009)
The paper critically reviews the categories with which the ethos of announcers of the media is built. It defines this ethos as an adaptation mechanism, which contextualizes the discourse of the speakers and guide public expectations. Then proposes its study understanding it as a moral iconic sign, constructed from abductive semiotic processes.